Pola Komunikasi Budaya Mahasiswa Rantau Dalam Menghadapi Culture Shock (Studi Kasus Mahasiswa Bima Di Kota Makassar) - jusmika, Jusmika; hadawiah, hadawiah; Zelfia, Zelfia (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Jusmika. 2022. “Patterns of Cultural Communication of Overseas Students in Facing Culture Shock (Case Study of Bima Students in Makassar City)”. (Supervised by Hadawiah and Zelfia) Thesis. Department of Communication Studies, Faculty of Letters, Muslim University of Indonesia. Culture shock occurs when individuals enter a new environment with a different culture, so the habits, norms, customs and values ​​that they have known so far cannot be applied in the new environment where they live. This phenomenon occurs in Bima overseas students. The aims of this study are 1. To determine the cultural communication patterns of Bima students in dealing with Culture shock while wandering in the city of Makassar 2. To determine the adaptation process of Bima overseas students in Makassar City. This study uses a qualitative method with the object of research, namely the Bima overseas students in Makassar City. The data collection used in this study used in-depth and semi-structured interviews to obtain results and complete information as required by the researcher. The results of this study are the cultural communication pattern of Bima students in dealing with Culture shock in Makassar City in this study is a primary communication pattern where the process of conveying thoughts or ideas by Bima students to their environment uses symbols as the medium, and students who experience the greatest culture shock are experienced by students. immigrants who are still categorized as new students.